Assessment Of Dietary Intake And Health Issues Among Obese Adults In District Srinagar Of Ut Jammu And Kashmir. - Irshad, Naila; Sumera, (International Journal of Psychosocial Rehabilitation, 2020)
Obesity is a compound, unending disease with numerous causes that lead to the development of metabolic diseases. Body fat itself is not an ailment, but it can change the way it functions once it gets accumulated in excess inside the body. These changes are progressive and get worse over time and thus lead to adverse health effects. A study on obesity and its complications and dietary assessment was carried out in District Srinagar of UT J&K, using a self-structured questionnaire. A sample of 150 obese individuals from both sexes in the age group of 25-65 years was selected by the purposive random sampling technique. The sample size was limited to 150 individuals because of the financial paucity. It was found that there were various complications associated with obesity and that the intake of energy and fats was found to be more than the recommendations (RDA) given by the Indian Council of Medical Research (ICMR). Furthermore, the intake of proteins was more or less in terms of the RDA.